2005
DOI: 10.5014/ajot.59.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Parents’ Use of Strategies To Promote Social Participation of School-Age Children With Acquired Brain Injuries

Abstract: Understanding how families use and integrate strategies within the context of their daily lives and what factors influence strategy use may provide practitioners with insights needed to support families in promoting their children's social participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 40 publications
7
67
1
Order By: Relevance
“…Some of these strategies directly related to the sensory factors of the activity or environment, whereas others were intended to reduce behavioral responses associated with the sensory factors through preparation, routine, and increasing the child's perception of control. Bedell, Cohn, and Dumas (2005) reported similar findings in a study of parents with children who had acquired brain injuries. Although several of the strategies were similar, the concept of anticipatory planning or preparation was central to both studies.…”
Section: Discussionsupporting
confidence: 71%
“…Some of these strategies directly related to the sensory factors of the activity or environment, whereas others were intended to reduce behavioral responses associated with the sensory factors through preparation, routine, and increasing the child's perception of control. Bedell, Cohn, and Dumas (2005) reported similar findings in a study of parents with children who had acquired brain injuries. Although several of the strategies were similar, the concept of anticipatory planning or preparation was central to both studies.…”
Section: Discussionsupporting
confidence: 71%
“…Even in the case of drug studies, an over-reliance on RCTs is counter to the goals of the initial EBP guidelines by Guyatt and colleagues (Guyatt et al, 2000). A narrow definition of "evidence" also excludes potentially useful information from qualitative studies, which have made an important contribution in areas such as the study of long-term psychosocial outcomes from TBI (e.g., Bedell, Cohn, & Dumas, 2005).…”
Section: Group Intervention Studiesmentioning
confidence: 99%
“…Previous studies have shown that during daily routines, caregivers implement strategies matched to child characteristics for children with acquired brain injury (Bedell, Cohn, & Dumas, 2005), attention deficit hyperactivity disorder (Segal, 2000), and developmental delays (Bernheimer & Weisner, 2007).…”
mentioning
confidence: 99%